Pengaruh Kinerja Keuangan dan Struktur Modal terhadap Nilai Perusahaan Basic Industry and Chemical Periode 2013-2017 - Sari, Devy Kurnia; Paramita, R.A. Sista (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This research is to examine the effect of profitability, leverage, and capital structure on firm value. The type of research is quantitative research. Research object at the basic industry and chemical sector in Indonesia Stock Exchange from 2013 to 2017. The dependent variable in this research is firm value. The independent variables in this research are profitability, leverage, and capital structure. Sampling is collected by using a purposive sampling method that produces 29 companies as a sample from a population of 60 companies. Data collection techniques used are literature study and documentation. The statistical analysis used in this study was using SPSS. The model used to test the relationship between independent variables with dependent variables is a multiple linear regression analysis. The results of the analysis show that profitability has a positive effect on firm value. On the other hand, leverage has a negative effect on firm value. In contrast, the capital structure does not affect the firm value. Therefore, the implication of this research for companies is that the companies can use profitability and leverage to know their firm value and increase it. Also, this research implies that investors can use profitability and leverage to make investment decisions for investors.